The inflammatory pathogenetic pathways of Fabry nephropathy - Feriozzi. Sandro (2024)
The high variability in clinical features and outcomes observed in monogenic diseases like Fabry disease suggeststhe presence of additional pathogenetic pathways beyond the lysosomal deposition of Gb3 and Lyso-GB3.Research indicates that the deposition of Gb3 and Lyso-Gb3 can stimulate the inflammatory processes.Mononuclear immune-competent cells exposed to Gb3 deposition exhibit surface adhesion molecules and releasepro-inflammatory and fibrotic cytokines such as IL β, TNFα, and TGFβ, culminating in the activation ofinflammatory cascades associated with oxidative stress, apoptotic mechanisms maintained by renal residents andinfiltrating cells, leading to chronic inflammation and tissue fibrosis. Furthermore, in another avenue of inquiry(termed Agalopathy), the mutated galactosidase alpha gene can result in the production of an altered alphagalactosidaseA enzyme, inducing endoplasmic reticulum stress and triggering the unfolded protein response(UPR) in an effort to prevent the production of altered proteins. The UPR, in turn, instigates the release of proinflammatorycytokines, thereby contributing to the inflammatory milieu. Experimental findings have demonstratedthat the pathogenetic mechanisms activated by Gb3 and Lyso Gb3 deposition can become independent from theinitial stimulus and may exhibit limited responsiveness to therapy. Cellular pathway alterations can persist posttherapyor gene correction. Moreover, biochemical and histological lesions characteristic of Fabry disease manifestin the absence of Gb3 in the Zebrafish experimental model. This review endeavors to describe the role of theseprocesses in Fabry nephropathy and aims to synthesize the available evidence on the pathogenesis of renaldamage.